Guidelines for coastal resource co-management in the Caribbean : communicating the concepts and conditions that favour success - McConney, P. (Caribbean Conservation Association BridgetownBB, 2003)
Aims to understand the conditions required for establishing and sustaining successful co-management of coastal resources in the Caribbean and to ensure that integrated coastal management is done in a way that involves and benefits those who depend on the resources of the coastal areas, especially where there is poverty.